1971
DOI: 10.1083/jcb.51.2.484
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Biochemical Changes in Rat Synaptosome Fractions During Neonatal Development

Abstract: A biochemical and quantitative morphologic study of presynaptic endings during postnatal development was carried out in subcellular fractions from cerebral cortex of 1, 4, 8, 12, and 18 day old and adult rats . Crude mitochondrial fractions were subfractionated in Ficoll gradients and all resulting fractions were examined in the electron microscope . Presynaptic terminals and other intact processes were counted . Protein content and enzyme activities were assayed in the fractions and in total brain homogenate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
1

Year Published

1973
1973
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(20 citation statements)
references
References 23 publications
4
15
1
Order By: Relevance
“…A function of neurotransmitter has been proposed for TRH on the basis of its wide distribution throughout the brain (1, 2), its localization in nerve endings (22), and its effects on behavior (23). During the first month of life, there is an active myelin formation, a marked growth of axons and dendrites from neurons (24), a progression of synaptic contacts (25) and a large increase of various enzyme activities in the brain (26). The physiological influence of TRH on the brain may be of importance during this period of time.…”
Section: Discussionmentioning
confidence: 99%
“…A function of neurotransmitter has been proposed for TRH on the basis of its wide distribution throughout the brain (1, 2), its localization in nerve endings (22), and its effects on behavior (23). During the first month of life, there is an active myelin formation, a marked growth of axons and dendrites from neurons (24), a progression of synaptic contacts (25) and a large increase of various enzyme activities in the brain (26). The physiological influence of TRH on the brain may be of importance during this period of time.…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been shown that synaptic curvature varies with age, young material (up to 15 days post-natally) exhibiting a greater range of curved synapses than older material [17], Other parameters, such as vesicle num bers per terminal, increase with age [19], while the length of the post-synaptic thicken ing fluctuates, as does the mean axial ratio of the pre-synaptic terminal [3,17].…”
Section: Introductionmentioning
confidence: 99%
“…To estimiiate the rate of relaxation of triceps surae after cessatioin of electrical stimiiulation of posterior tibial nerve, the timiie required for tension to fall from the deflectioni point at the end of the tetanic plateau to one-halfthe plateau tension value (T1,2 relaxation time) (6) (14). Osmium tetroxide was used instead of Dalton's fixative.…”
mentioning
confidence: 99%